Selectividad del cultivo de maíz (Zea mays L.) a la aplicación del herbicida Nicosulfuron en diferentes etapas de desarrollo - Moyano Cercado, Mario Xavier (2020)
Maize (Zea mays L.) is in the most important group of grasses for human consumption, serving both for direct feeding and animal husbandry. Currently, around the world 645 414 836.10 tons of corn are produced on average, the main exporters of this product are the United States, Argentina and France. The main global consumers of the grass are Mexico, China, Indonesia and India. In Ecuador they currently sow approximately 400 868 ha, the areas of greatest production are: Los Ríos (177 194 ha), Manabí (112 716 ha), Guayas (50 164 ha) and the rest of the country (48 794 ha) (MAGAP, 2012). In the last decade, the use of hybrids has intensified due to their high levels of productivity; however, for hybrids to display their full potential for performance, efficient technological management and appropriate climatic conditions are necessary (ALVARES, 2004). In the technological management of corn cultivation, weed control is a factor of great importance; because the presence of weeds interferes in the normal development of the crop. Nicosulfuron is a herbicide that controls a wide range of grass weeds and some broadleaf weeds (dicotyledons), but especially the treadmill. Weeds treated with Nicosulfuron show growth arrest, followed by chlorosis or yellowing, until death. Its action is slow and symptoms can be observed from the fifth day after application. On the other hand, weed control with Nicosulfuron is excellent in its application before 30 days after sowing, reducing its effects on dates after this time